The Sebald Phenomenon: A New Volume of Essays on the Critical Historiography of W.G. Sebald (KULT_online, 2008)
W.G. Sebald. History - Memory - Trauma contains selected findings from an international conference held at Davidson College from 13-16 March, 2003 that explore critical interpretations of Sebald's work from an historiographic perspective. The volume is the first in the new series "Interdisciplinary German Cultural Studies" released by De Gruyter Verlag and edited by Scott Denham, Irene Kacandes, and Jonathan Petropoulos.